THE ROLE OF MOTIVATION IN HUMAN ACHIEVEMENT - Hamrokulova Jasmina Ozodovna (TADQIQOTLAR, 2025)
Abstract Motivation is one of the most powerful psychological and spiritual forces that govern human behavior. It does not only determine the extent of one’s efforts, but also influences resilience, creativity, and overall life satisfaction. This paper explores the multifaceted and deeply important role of motivation in shaping human potential, arguing that it functions as the central element that connects ambition, perseverance, and personal growth. By analyzing motivation from psychological, emotional, and spiritual perspectives, the essay highlights how cultivating strong intrinsic motivation enables individuals to overcome adversity and achieve self-actualization, fulfilling both inner and outer purposes of life.